Advertisements as Cultural Texts: Looking at Homemakers and Mothers in Mandate Palestine. Issue 3 (3rd July 2022) - Marnin-Distelfeld, Shahar
Abstract : This article examines representations of homemakers and mothers occurring in ads appearing during Mandate Palestine. It is based on comprehensive research of about 150 ads, from dailies, women's magazines, and manuals published in Hebrew at that time. In all ads, a feminine figure appears as the main character. The ads are analyzed, extracting the meanings inherent in them regarding the role and social status of the Hebrew homemaker, as a key to understanding the worldviews prevalent in the Yishuv. This premise perceives the ads as cultural texts, aiming for an effective communication with their audience. Decoding these ads is done according to theories taken from semiotics and cultural studies in relation to historical knowledge of Hebrew homemakers of the Yishuv. Three dominant ideologies were explored underlying the ads: Hebrew nationalism, modern domesticity, and the ideology of science. The strategies used by advertisers are also discussed, in themselves a significant tool for constructing meaning.